2022
DOI: 10.3389/fendo.2022.872527
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thyroglobulin in Preoperative and Postoperative Evaluation of Patients With Differentiated Thyroid Cancer

Abstract: Thyroglobulin (Tg) is secreted by thyroid follicular cells and stored in the thyroid follicular lumen as a component of thyroid hormone. It is known that both benign and well-differentiated malignant thyroid tissue can secrete Tg. In recent years, growing lines of evidence have shown that Tg plays an important role in the diagnosis and metastasis of preoperative differentiated thyroid carcinoma (DTC). The levels of Tg, whether in the serum or in a fine-needle aspiration washout fluid, are usually viewed as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 110 publications
0
15
0
1
Order By: Relevance
“…Serum Tg can be secreted by normal thyroid follicular epithelial cells or well-differentiated DTC cells and is affected by postoperative residual thyroid tissue, serum TSH, and TgAb levels. Previous studies have shown that changes in serum psTg levels are an important factor in disease remission, persistence, recurrence, and prognosis after DTC treatment and are an important indicator in efficacy evaluations, disease monitoring, and determining prognoses in long-term follow-up (11)(12)(13). In this study, multivariate analysis indicated that psTg was an independent factor for predicting ER (OR: 1.325; 95% CI: 1.135-1.547; P<0.001), which was consistent with previous research by Webb et al in a meta-analysis of more than 4,000 cases of DTC (14).…”
Section: Discussionmentioning
confidence: 99%
“…Serum Tg can be secreted by normal thyroid follicular epithelial cells or well-differentiated DTC cells and is affected by postoperative residual thyroid tissue, serum TSH, and TgAb levels. Previous studies have shown that changes in serum psTg levels are an important factor in disease remission, persistence, recurrence, and prognosis after DTC treatment and are an important indicator in efficacy evaluations, disease monitoring, and determining prognoses in long-term follow-up (11)(12)(13). In this study, multivariate analysis indicated that psTg was an independent factor for predicting ER (OR: 1.325; 95% CI: 1.135-1.547; P<0.001), which was consistent with previous research by Webb et al in a meta-analysis of more than 4,000 cases of DTC (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, postoperative serum TG monitoring is necessary to detect potential lymph node metastases. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, postoperative serum TG monitoring is necessary to detect potential lymph node metastases. [47] Voice change is one of the most common complications of thermal ablation and may result from recurrent laryngeal nerve dysfunction due to thermal effects and bleeding. [48] The results of this study showed that the complication rates of the 3 thermal ablation methods were relatively low, with no significant difference (P > .05), which may be related to the frequency of ablation, type of equipment, operator experience, and technology.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of thyroid cancer is differentiated thyroid cancer (DTC) [1]. The disease generally has a good prognosis, but the recurrence can affect up to 30% of patients within 10 years of initial diagnosis [1].…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of thyroid cancer is differentiated thyroid cancer (DTC) [1]. The disease generally has a good prognosis, but the recurrence can affect up to 30% of patients within 10 years of initial diagnosis [1]. Total thyroidectomy with "therapeutic" cervical lymph node dissection for involved lymph nodes is the standard of care.…”
Section: Introductionmentioning
confidence: 99%